Yellow fever vaccine protects mice against Zika virus infection - Ana C. Vicente Santos; Francisca H. Guedes-; Carlos H. Dumard; Vivian N. S. Ferreira; Igor P. S. da Costa; Ruana A. Machado; Fernanda G. Q. Barros-Aragão; Rômulo L. S. Neris; Júlio S. dos-Santos; Iranaia Assunção-Miranda; Claudia P. Figueiredo; André A. Dias; et al. (Public Library of Science (PLoS), 2021)
Zika virus (ZIKV) emerged as an important infectious disease agent in Brazil in 2016. Infection usually leads to mild symptoms, but severe congenital neurological disorders and Guillain-Barré syndrome have been reported following ZIKV exposure. Creating an effective vaccine against ZIKV is a public health priority. We describe the protective effect of an already licensed attenuated yellow fever vaccine (YFV, 17DD) in type-I interferon receptor knockout mice (A129) and immunocompetent BALB/c and SV-129 (A129 background) mice infected with ZIKV. YFV vaccination provided protection against ZIKV, with decreased mortality in A129 mice, a reduction in the cerebral viral load in all mice, and weight loss prevention in BALB/c mice. The A129 mice that were challenged two and three weeks after the first dose of the vaccine were fully protected, whereas partial protection was observed five weeks after vaccination. In all cases, the YFV vaccine provoked a substantial decrease in the cerebral viral load. YFV immunization also prevented hippocampal synapse loss and microgliosis in ZIKV-infected mice. Our vaccine model is T cell-dependent, with AG129 mice being unable to tolerate immunization (vaccination is lethal in this mouse model), indicating the importance of IFN-γ in immunogenicity. To confirm the role of T cells, we immunized nude mice that we demonstrated to be very susceptible to infection. Immunization with YFV and challenge 7 days after booster did not protect nude mice in terms of weight loss and showed partial protection in the survival curve. When we evaluated the humoral response, the vaccine elicited significant antibody titers against ZIKV; however, it showed no neutralizing activity in vitro and in vivo. The data indicate that a cell-mediated response promotes protection against cerebral infection, which is crucial to vaccine protection, and it appears to not necessarily require a humoral response. This protective effect can also be attributed to innate factors, but more studies are needed to strengthen this hypothesis. Our findings open the way to using an available and inexpensive vaccine for large-scale immunization in the event of a ZIKV outbreak. Author summary Zika virus (ZIKV) is as an important infectious that may result in severe congenital neurological disorders. Our study reports that the current attenuated yellow fever vaccine is effective in immunizing against the infection caused by the Zika virus, due to the similarity between the two viruses. To study the efficacy of the vaccine, we used different mouse strains, including both animals with a healthy immune system (immunocompetent) and animals with compromised immune systems and therefore more susceptible to viral (immunocompromised) infections. The vaccine was given subcutaneously, as it does in humans. The animals were inoculated with the Zika virus directly into the brain-a protocol normally adopted in vaccine studies to simulate a high lethality infection. In all cases, the vaccinated mice developed a high degree of protection against Zika infection. Altogether, we demonstrate that the YFV vaccine elicits an immune response that protects against cerebral infection by ZIKV. Our findings suggest the possibility of using an available and inexpensive vaccine for large-scale immunization in the event of a ZIKV outbreak.